Hubungan Kekuatan Otot dengan ADL pada Pasien Stroke - Dewi Nur Sukma; Baiq Ruli Fatmawati; Zaenal Arifin (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2022)
Background: Stroke is a condition that occurs when the blood supply to the brain is disrupted or reduced due to a blockage. It can caused temporary or permanent loss of brain function in movement, thinking, speech, or sensation. This limitation causes stroke patients to depend on their family or others to fulfill their basic needs to carry out activities of daily living. Objective: The purpose of this study is to determine the relationship between Muscle strength and activities of daily living in stroke patients.Methods: The design used in this research is descriptive analytic with a cross sectional approach. Data analysis using Chi Square Test.Results: The results showed that respondents who experienced a mild level of dependence on Daily Living Activities were 21 people (84%) and respondents with moderate levels of dependence on Activities of Daily Living  were 4 people (16%) from all of the 25 respondents. , the test results obtained p- value = 0.041 (0.05).Conclusion: So it can be concluded that there is a relationship between Muscle strength and activities of daily living  in stroke patients. For further researchers, it is expected to conduct further research on other variables that can affect the daily life activities of stroke patients..Keywords: Activities of Daily Living, Muscle strength, Stroke